1985
DOI: 10.1083/jcb.100.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pre- and postsynaptic factors of the serotonin system in rabbit retina.

Abstract: [3H]Serotonin is accumulated by a specific set of amacrine cells in the rabbit retina. These cells also accumulate the neurotoxin, 5,7-dihydroxytryptamine, and show signs of necrosis within 4 h of in vivo exposure to the drug. Biochemical analysis of [3H]serotonin uptake reveal a sodium-and temperature-dependent, high affinity uptake system with a Km of 0.94 #M and Vmax of 1.08 pmol/mg protein/min. [3H]Tryptophan is also accumulated in rabbit retinal homogenates by a high affinity process. Accumulated [3H]sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
4
36
0
Order By: Relevance
“…114 Serotonin also inhibits the release of thyrotropin releasing hormone from rat retinas. 115 5-HT 1 receptors are present on rabbit retinal membranes, 92 and mRNA for 5-HT 1A is present in rabbit and rat retinas. 116,117 The effects of the 5-HT 1A agonist 8-hydroxy-2-(di-npropylamino) tetralin(8-OH-DPAT) are particularly well-characterized in rabbit retinas.…”
Section: Retinopetal Axons Containing Serotoninmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Serotonin also inhibits the release of thyrotropin releasing hormone from rat retinas. 115 5-HT 1 receptors are present on rabbit retinal membranes, 92 and mRNA for 5-HT 1A is present in rabbit and rat retinas. 116,117 The effects of the 5-HT 1A agonist 8-hydroxy-2-(di-npropylamino) tetralin(8-OH-DPAT) are particularly well-characterized in rabbit retinas.…”
Section: Retinopetal Axons Containing Serotoninmentioning
confidence: 99%
“…[89][90][91][92][93] These low levels of endogenous serotonin suggest that serotonin is used as a neurotransmitter by a sparse population of retinopetal axons rather than amacrine cells. Serotonin is synthesized from tryptophan in two steps by tryptophan hydroxylase and amino acid decarboxylase.…”
Section: Retinopetal Axons Containing Serotoninmentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine, 5-HT) has been reported to be present in the retina of several vertebrates (9)(10)(11). The existence of the specific uptake systems for 5-HT or a closely related indoleamine in the vertebrate retinas suggested that indoleamines are taken up and released for neurotransmission.…”
mentioning
confidence: 99%
“…This system is characterized by ligand specificity, Na+ and temperature dependence, antagonizability by known blockers (nortriptyline, imipramine, and desipramine), and saturable and high-affinity uptake kinetics. In particular, the Km and Vma values are well within the range of such parameters measured for 5-HT-uptake systems in the central nervous system and blood platelets (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 79%
“…Although the physiology and pharmacology of a number of neurotransmitter transport systems including that for serotonin have been extensively studied (6)(7)(8)(9)(10)(11)(12)(13), little is known about the biochemistry and molecular biology of any of these systems. With the hope of attaining such information, we report here the use of gene transfer (14)(15)(16)(17) in the establishment and identification of a clonal mouse fibroblast cell line, L-S1, that stably expresses a presumptively human highaffinity uptake system for serotonin (5-HT).…”
mentioning
confidence: 99%